The last hurrah? : soft money and issue advocacy in the 2002 congressional elections - Magleby, David B.; Monson, J. Quin (Brookings Institution Press, 2004)
The Last Hurrah presents a comprehensive analysis of the role soft money and issue advocacy play in congressional elections. It also documents the extent of campaigning done through the mail, on the telephone, and in person in competitive races. David Magleby and J. Quin Monson provide detailed coverage of the overall trends of the historic 2002 midterm election in which the president¿s party leveraged its strengths to retake the Senate and make gains in the House. They pay particular attention to the role of President Bush and his political operation in candidate recruitment, fundraising, a.